Regieren an der Peripherie Amerika zwischen Kolonien und unabhängigen Republiken - Rinke, Stefan; Contreras Saiz, Mónika; Hölck, Lasse (Historamericana, 2022)
The articles collected in this volume use case studies to examine the specific problems and possibilities of governance in the Latin American periphery, covering a period ranging from the pre-Hispanic period to the first half of the 20th century.